Hand eczema in children referred for patch testing: North American Contact Dermatitis Group Data, 2000–2016. (31st March 2021) - Silverberg, J.I.; Warshaw, E.M.; Maibach, H.I.; DeKoven, J.G.; Taylor, J.S.; Atwater, A.R.; Sasseville, D.; Zug, K.A.; Reeder, M.J.; Fowler, J.F.; Pratt, M.D.; Fransway, A.F.; et al.
Summary: Background: Little is known about the aetiologies and relevant allergens in paediatric patients with hand eczema (HE). Objectives: To characterize the aetiologies and determine the proportion of positive and currently relevant allergens in children/adolescents (age < 18 years) with HE referred for patch testing. Methods: A retrospective analysis (2000–2016) of North American Contact Dermatitis Group data was performed. Results: Of 1634 paediatric patients, 237 (14·5%) had involvement of the hands. Final physician diagnoses included allergic contact dermatitis (49·4%), atopic dermatitis (37·1%) and irritant contact dermatitis (16·9%). In multivariable logistic regression models, employment was the only association with increased odds of any HE or primary HE. Children with HE vs. those without HE had similar proportions of positive patch tests (56·1% vs. 61·7%; χ 2 ‐test, P = 0·11). The five most common currently relevant allergens were nickel, methylisothiazolinone, propylene glycol, decyl glucoside and lanolin. In multivariable logistic regression models of the top 20 relevant allergens, HE was associated with significantly higher odds of currently relevant reactions to lanolin, quaternium‐15, Compositae mix, thiuram mix, 2‐mercaptobenzathiazole and colophony. The allergens with the highest mean significance‐prevalence index number were methylisothiazolinone, carba mix, thiuram mix, nickel and methylchloroisothiazolinone/methylisothiazolinone. Conclusions: Children with HE who were referred for patch testing had a high proportion of positive patch tests, which was similar to the proportion found in children without HE. Children with HE had a distinct and fairly narrow profile of currently relevant allergens. Abstract : What is already known about this topic? Hand eczema is a heterogeneous disorder, with overlap of irritant exposures, allergic exposures and atopic predisposition. Few studies have examined the aetiologies of hand eczema in children. What does this study add? Children with hand eczema who were referred for patch testing had a high proportion of positive patch tests, which was similar to the proportion in children without hand eczema. Children with hand eczema had a distinct and fairly narrow profile of currently relevant allergens. Employment was the strongest risk factor for hand eczema in children. Linked Comment: A. Schnuch. Br J Dermatol 2021; 185 :17–18 .